Prospects of Storage and Pumped-Storage Hydropower for Enhancing Integrated Nepal Power Systems - Sah, Neeraj Kumar; Uprety, Madhab; Bhandari, Sangharsha; Kharel, Prativa; Suman, Saurav; Maskey, Ramesh Kumar (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
An Integrated Power System (IPS) should have electrical energy generating plants for base load (e.g., nuclear and thermal plants) and peak load (e.g., hydropower plants) so that they can work in coordination in such a way that the demand is met in time. In Nepal, the Integrated Nepal Power System (INPS) is a hydro-dominated system where the base and intermediate power demands are covered primarily by run-of-river hydropower plants and the peak demand by seasonal storage and several diesel power plants of lower capacity. The INPS should have sufficient natural storage and forced storage power plants to improve the system’s reliability. On top of that, daily peak electrical demand could also be adequately covered by demand-side management, using a pumped-storage hydropower plant that can employ a system’s surplus energy during low demand period for pumping. To rectify this extreme imbalance of installed capacity in Nepal, this paper explores the prospect of storage and pumped-storage power plants for enhancing INPS. A case study of Rupa-Begnas pumped-storage hydropower is highlighted for these purposes. DOI: http://dx.doi.org/10.3126/hn.v15i0.11290 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 37-41